2020
DOI: 10.1001/jama.2020.6266
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Co-infection Between SARS-CoV-2 and Other Respiratory Pathogens

Abstract: Background: Since December 2019, the coronavirus disease 2019 (COVID-19) has infected more than 12,310322,000 people and killed over 556,000 people worldwide. However, Differential diagnosis remains di cult for suspected cases of COVID-19 and need to be improved to reduce misdiagnosis. Methods: Sixty-eight cases of suspected COVID-19 treated in Wenzhou Central Hospital from January 21 to February 20, 2020 were divided into con rmed and COVID-19-negative groups based on the results of real-time reverse transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

50
732
11
37

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 711 publications
(830 citation statements)
references
References 1 publication
50
732
11
37
Order By: Relevance
“…Another finding that has been recently reported is the evidence of coinfection with SARS‐CoV‐2 and other respiratory pathogens. 9 We found several viral coinfections among patients testing positive for COVID‐19, which suggests that when emergency physicians evaluate patients for possible viral illness, a positive test for another pathogen should not exclude the workup for COVID‐19 in the correct clinical context.…”
Section: Overall (N = 100) Admitted (N = 24) Not Admitted (N = 76)mentioning
confidence: 86%
“…Another finding that has been recently reported is the evidence of coinfection with SARS‐CoV‐2 and other respiratory pathogens. 9 We found several viral coinfections among patients testing positive for COVID‐19, which suggests that when emergency physicians evaluate patients for possible viral illness, a positive test for another pathogen should not exclude the workup for COVID‐19 in the correct clinical context.…”
Section: Overall (N = 100) Admitted (N = 24) Not Admitted (N = 76)mentioning
confidence: 86%
“…In contrast with other series that describe up to 20% of respiratory virus coinfection. (12) As described in Chinese and Italian reports, higher ferritin and lactic dehydrogenase levels at admission were also significantly associated with critical pneumonia. (13,14) Moreover, we found that higher IL-6 concentration was significantly associated with critical pneumonia and the need for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 80%
“…The median follow-up day was 8 (IQR 5. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. For the 9 (27%) patients still in the hospital, we have at least 6 days of follow-up.…”
Section: Complicationsmentioning
confidence: 99%
“…So, testing of SARS-CoV-2 should been done for patients with non-SARS-CoV-2 respiratory pathogens in high incidence of COVID-19 region. [15] The detection of non-SARS-CoV-2 respiratory pathogens by multiplex PCR may help to assess individual the risk of COVID-19 in areas of low transmission. [16] Because of the highly infectious nature of SARS-CoV2, the suspected COVID-19 cases were all isolated and monitored in a single-person single-room isolation ward.…”
Section: Discussionmentioning
confidence: 99%